Multi-sensor platform for real time measurements of honey bee hive parameters. (May 2019) - Cecchi, S.; Terenzi, A.; Orcioni, S.; Spinsante, S.; Mariani Primiani, V.; Moglie, F.; Ruschioni, S.; Mattei, C.; Riolo, P.; Isidoro, N.
Abstract: Honey bees ( Apis mellifera L. ) are well-known insects that have positive effects on the environment and on the human life. They are so important that the decline of honey bee colonies happened in the last years has triggered an increasing interest for their safeguard. In this context, the proposed work aims at developing a multi-sensor platform to monitor the beehives' conditions in real time, based on the measurement of sounds emitted by the bees, temperature, humidity, CO2, weight inside the beehive, and weather conditions outside the hive. In this paper, a detailed description of the multi-sensor platform is reported and its application in a real scenario is presented.